2020
DOI: 10.1186/s12881-020-01165-0
|View full text |Cite
|
Sign up to set email alerts
|

Wilson disease, ABCC2 c.3972C > T polymorphism and primary liver cancers: suggestions from a familial cluster

Abstract: Background Polymorphisms in genes modulating xenobiotics metabolism, in particular the ABCC2 c.3972C > T single nucleotide polymorphism (SNP) at exon 28, have been suggested to increase primary liver cancer (PLC) risk. Conversely, the occurrence of PLCs in Wilson disease patients is a rare event, in contrast with the occurrence observed in other chronic liver diseases. Here we report the clinical case of five siblings carrying the ABCC2 c.3972C > T SNP; three of them were affected by Wilson disease and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Here, the frequency of ABCC2 variant c.3972T (rs3740066) allele T was significantly higher in CCA patients (39.2%) compared to healthy controls, suggesting that ABCC2 c.3972C > T (rs3740066) polymorphism is associated with an increased risk of CCA [ 28 ]. Brandi et al reported an interesting example of this SNP [ 68 ]. The authors conducted genotyping of five siblings from the same family and all five were identified as ABCC2 rs3740066 carriers.…”
Section: Resultsmentioning
confidence: 99%
“…Here, the frequency of ABCC2 variant c.3972T (rs3740066) allele T was significantly higher in CCA patients (39.2%) compared to healthy controls, suggesting that ABCC2 c.3972C > T (rs3740066) polymorphism is associated with an increased risk of CCA [ 28 ]. Brandi et al reported an interesting example of this SNP [ 68 ]. The authors conducted genotyping of five siblings from the same family and all five were identified as ABCC2 rs3740066 carriers.…”
Section: Resultsmentioning
confidence: 99%
“…This research suggests that carcino-genesis may arise from liver damage, subsequently leading to chronic inflammation and cirrhosis due to chronic copper accumulation [ 10 , 11 ]. Recent research indicates that certain genetic variations, particularly the c.3972C > T variant at exon 28 of the ABCC2 gene, may play a role in enhancing susceptibility to primary liver cancer, including both HCC and IHCC [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 By performing next generation sequencing in patients affected by DJS, several naturally occurring variants were found in ABCC2 sequence, including exon skipping, nonsense, missense, small deletions or insertions, and splice site variations, causing truncated and dysfunctional MRP2. [11][12][13][14][15] Previous studies have yielded initial insight into the mechanisms Open access by which DJS-causing variants in the ABCC2 gene alter MRP2 function, resulting in the inhibition of bile acid excretion as well as ineffective transport of bilirubin out of hepatocytes. 16 These findings are related to aberrant protein synthesis, and for missense variants to alter sublocalisation or secretory activity, which may cause MRP2 to remain in the endoplasmic reticulum rather than moving to the canalicular membrane, or finally to increased protein degradation.…”
Section: What This Study Addsmentioning
confidence: 99%